The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2478/v10060-008-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Ploughed-on terraces in loess landscape of strongly developed high plains

Abstract: Abstract:Ploughed-on terraces in loess landscape of strongly developed high plains. The ploughed-on terraces were one of the techniques for agricultural use of steep slopes in loess landscapes of developed high plains, the example of which is described fragment of the valley in Bartłomiejowice near Nałęczów. Giving up the agricultural use makes disappearance of those anthropogenic-erosion relief forms in the landscape structure. The authors postulate to protect -by restoring the meadow-pasture use -the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Most lynchets studied in Ethiopia are very similar to those in NW Europe, where it has also been shown that they resulted from soil translocation by tillage and water erosion of temporarily bare soils (Bollinne, 1971;Gerlach, 1963;Ozer, 1969;Patro et al, 2008;Poesen et al, 1997;Van Oost and Govers, 1998). This study did not consider risers of non-agricultural origins such as brick earth excavations, river terraces, and road or river banks.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Most lynchets studied in Ethiopia are very similar to those in NW Europe, where it has also been shown that they resulted from soil translocation by tillage and water erosion of temporarily bare soils (Bollinne, 1971;Gerlach, 1963;Ozer, 1969;Patro et al, 2008;Poesen et al, 1997;Van Oost and Govers, 1998). This study did not consider risers of non-agricultural origins such as brick earth excavations, river terraces, and road or river banks.…”
Section: Discussionmentioning
confidence: 84%
“…As observed in Ethiopia, tillage erosion by simple tools, in addition to sediment transport due to water erosion, can lead to fast soil accumulation in the lynchets (Chartin et al, 2011;De Alba et al, 2004). As the rate of tillage erosion is independent from slope length, imposing lynchets can also develop on narrow parcels, established along the contour, as shown elsewhere (Patro et al, 2008).…”
Section: Formation Process Of Lynchetsmentioning
confidence: 78%
See 1 more Smart Citation
“…possible way to stop or reduce the degrading effect of soil erosion. It is one of the oldest means of saving soil and water (Dorren and Rey 1998, Patro et al 2008, Schönbrodt-Stit et al 2013. Moreover, it is the most widely used soil conservation practice throughout the world (Hanway and Lafl en 1974, Mountjoy and Gliessman 1988, Sutikto and Chikamori 1993, Franti et al 1998, Ruecker et al 1998, Quine et al 1999, Kasai et al 2001, Yi et al 2017.…”
Section: Abstract: Determining the Spacing Of Ridge Terraces On Arablmentioning
confidence: 99%
“…Apart from their functions in material redistribution, they provide important biological corridors and places of increased biodiversity in tilled land, and they retain the surplus run‐off increasing the amount of water retained in the watershed and, last but not least, represent a key landscape component resulting from long‐term agricultural management. A common occurrence of lynchets in the agricultural landscape, both historical and present, has been described worldwide: in France (Chartin et al ., ; Froehlicher et al ., ), Belgium (Nyssen et al ., ), Poland (Patro et al ., ), Germany (Moldenhauer et al ., ; Stolz, ; Larsen et al ., ), Spain (Poesen et al ., ), North America (Vieira & Dabney, ), South America (Dercon et al ., ) and Africa (Lewis, ; Nyssen et al ., ), most often in undulating dynamic landscapes with a prevalence of small farms. In Great Britain (Favis‐Mortlock et al ., ) and Denmark (Nielsen & Dalsgaard, ), prehistoric lynchets have been studied related to Celtic settlements.…”
Section: Introductionmentioning
confidence: 99%